2004
DOI: 10.1111/j.1365-2303.2003.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of tuberculous lymphadenitis by FNAC, microbiological methods and PCR: a comparative study

Abstract: Despite its usefulness in the diagnosis of tuberculous lymphadenitis, fine needle aspiration cytology (FNAC) faces several limitations, and its sensitivity and specificity are not well established. The diagnostic accuracy and limitations of FNAC were studied in comparison with conventional microbiological methods and polymerase chain reaction (PCR). Sixty patients with lymphadenopathy and a clinical diagnosis of tuberculous lymphadenitis were subjected to FNA. The aspirate was used for cytological examination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 16 publications
11
52
0
1
Order By: Relevance
“…Comparable observations have been reported in other studies (5,7,23). These findings are analogous to those reported for the use of FNA for the diagnosis of tuberculous lymphadenitis (2,8,15,27). Also, a recent study by Phillips et al (24) reports PCR as the most sensitive technique for confirming the presence of M. ulcerans in FNA of nonulcerative BU lesions.…”
Section: Discussionsupporting
confidence: 77%
“…Comparable observations have been reported in other studies (5,7,23). These findings are analogous to those reported for the use of FNA for the diagnosis of tuberculous lymphadenitis (2,8,15,27). Also, a recent study by Phillips et al (24) reports PCR as the most sensitive technique for confirming the presence of M. ulcerans in FNA of nonulcerative BU lesions.…”
Section: Discussionsupporting
confidence: 77%
“…13,18 This study had a lower false negative rate in TB diagnosis when compared to a study by Aljafari et al in Sudan where he found a false negative rate of 38% using a bigger gauge needle. 19 The difference, probably can be attributed to the differences in sizes of needles used, since the bigger the needle the higher the chances of haemorrhage distorting the cytological picture. There was an excellent kappa agreement of 0.85 between FNAC and histology results in the diagnosis of tuberculosis.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…FNAC of the lymph node was done under clinical guidance with a 23-gauge needle under aseptic conditions [6,7] . The aspirate was divided into 5 parts.…”
Section: Fine-needle Aspiration Cytologymentioning
confidence: 99%